2013
DOI: 10.1080/19466315.2013.791640
|View full text |Cite
|
Sign up to set email alerts
|

Current Practices, Challenges, and Statistical Issues With Product Safety Labeling

Abstract: Prescribing health care professionals are dependent on product labels to give them the information they need to appropriately prescribe drugs and monitor patients. A well-constructed label with accurate, meaningful, and easy-to-understand information is important for understanding the benefit-risk profile of the compound. Statisticians are uniquely qualified to help. Historically, statisticians have played a major role in defining the efficacy information provided in the label. Similar leadership is needed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…It is also possible that differences existed across trials in terms of how adverse events were collected (e.g. active vs. passive elicitation) and in the definition of ‘treatment‐emergent’ . It is important to note that the PASI results were based on the nonresponder imputation, in which all patients who discontinued the study for any reason including adverse events were counted as nonresponders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that differences existed across trials in terms of how adverse events were collected (e.g. active vs. passive elicitation) and in the definition of ‘treatment‐emergent’ . It is important to note that the PASI results were based on the nonresponder imputation, in which all patients who discontinued the study for any reason including adverse events were counted as nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…active vs. passive elicitation) and in the definition of 'treatment-emergent'. 24 It is important to note that the PASI results were based on the nonresponder imputation, in which all patients who discontinued the study for any reason including adverse events were counted as nonresponders. Thus, the PASI results already combine elements of efficacy and tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…Identical events will be classified both by diagnosis and symptom complexes. These difficulties are most problematic for nonserious adverse events (see Crowe et al 2013). One approach to aid investigators is to remind them to look at the way in which they previously reported an event for a specific person.…”
Section: Collection and Classification Of Data On Serious Adverse Eventsmentioning
confidence: 99%
“…It is the Aalen‐Johansen estimator that generalizes the Kaplan‐Meier estimator to multiple event types and nonparametrically estimates the so‐called cumulative incidence function P(AE in [0, t ]), accounting for both CEs and the usual censoring due to end of follow‐up. The Aalen‐Johansen estimator for the probability of AE occurrence is (Allignol et al and references therein) trueP^false(Tt,AEfalse)=uttrueP^false(T>ufalse)·aunu2.56804pt, where T is the time until occurrence of an AE or of a CE, trueP^false(T>ufalse) denotes the estimate of the probability of not experiencing an AE or the CE just prior to time u , and n u is the number of patients at risk of observing an AE or a CE just prior to u .…”
Section: Statistical Methodologiesmentioning
confidence: 99%